2023
DOI: 10.1172/jci163446
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages and microglia in glioblastoma: heterogeneity, plasticity, and therapy

Abstract: Glioblastoma (GBM) is the most aggressive tumor in the central nervous system and contains a highly immunosuppressive tumor microenvironment (TME). Tumor-associated macrophages and microglia (TAMs) are a dominant population of immune cells in the GBM TME that contribute to most GBM hallmarks, including immunosuppression. The understanding of TAMs in GBM has been limited by the lack of powerful tools to characterize them. However, recent progress on single-cell technologies offers an opportunity to precisely ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(100 citation statements)
references
References 114 publications
3
97
0
Order By: Relevance
“…2D). Collectively, these results suggest that lysosomes/endolysosomes are prominent cellular components of GBM tumor-associated macrophages (TAMs), a major, heterogeneous population of cells that are key to shaping immune microenvironment and mediating immunosuppression in GBM [18][19][20] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2D). Collectively, these results suggest that lysosomes/endolysosomes are prominent cellular components of GBM tumor-associated macrophages (TAMs), a major, heterogeneous population of cells that are key to shaping immune microenvironment and mediating immunosuppression in GBM [18][19][20] .…”
Section: Resultsmentioning
confidence: 99%
“…In-depth examination of the MC3 genes further corroborates the roles of endolysosomes in GBM pathogenesis and, specifically, in immunosuppression. First, we assessed the relationship between the 21 MC3 genes and a set of four genes representative of GBM’s immune suppressive microenvironment: the immunosuppressive TAM markers MRC1 (CD206) and CD163 18 and the immunosuppressive cytokines IL10 and TGFB1 18,20 , and found overwhelmingly positive correlations between these two groups of genes ( Fig. 4A-B, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The brain TME includes endothelial cells, pericytes, astrocytes, neurons, oligodendrocytes and immune cells. Although GBMs are known as 'cold tumors' with very little lymphocytic infiltration 3 , the GBM TME contains up to 40% of myeloid cells, which, as a whole, are referred to as tumorassociated macrophages (TAMs) and are known to create a supportive environment facilitating tumor proliferation, survival and migration 4,5 . TAMs are mainly constituted by brain resident parenchymal microglia (Mg), peripheral monocytes (Mo) and perivascular macrophages, known as border-associated macrophages (BAMs) [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, high lactate levels produced by the Warburg effect have been demonstrated as a key immunosuppressive metabolite in the tumor microenvironment (TME). 18 Research has shown that the Warburg effect leads to the formation of an immunosuppressive microenvironment by maintaining a low potential hydrogen value in the TME, 18,19 such as by polarizing tumor-associated macrophages to favor the M2 phenotype, 20,21 promoting the depletion of cytotoxic T cells, 22 and thereby promoting tumor progression. However, the role of the Warburg effect on other cells involved in tumor immunity has not been clearly reported, especially the role of the Warburg effect on the immune cell profile in the GBM immune microenvironment.…”
Section: Introductionmentioning
confidence: 99%